Peroxidase(s) in Environment Protection - Neelam Bansal; Shamsher S. Kanwar (The Scientific World Journal)
Industrial discharges of untreated effluents into water bodies and emissions into air have deteriorated the quality of water and air, respectively. The huge amount of pollutants derived from industrial activities represents a threat for the environment and ecologic equilibrium. Phenols and halogenated phenols, polycyclic aromatic hydrocarbons (PAH), endocrine disruptive chemicals (EDC), pesticides, dioxins, polychlorinated biphenyls (PCB), industrial dyes, and other xenobiotics are among the most important pollutants. Peroxidases are enzymes that are able to transform a variety of compounds following a free radical mechanism, thereby yielding oxidized or polymerized products. The peroxidase transformation of these pollutants is accompanied by a reduction in their toxicity, due to loss of biological activity, reduction in the bioavailability, or the removal from aqueous phase, especially when the pollutant is found in water. The review describes the sources of peroxidases, the reactions catalyzed by them, and their applications in the management of pollutants in the environment.